Comparison of Home and Ambulatory Blood Pressure Measurements in Association With Preclinical Hypertensive Cardiovascular Damage. Issue 2 (March 2019) - Lin, Ting-Tse; Juang, Jimmy Jyh-Ming; Lee, Jen-Kuang; Tsai, Chia-Ti; Chen, Chen-Huan; Yu, Wen-Chung; Cheng, Hao-min; Wu, Yen-Wen; Chiu, Yu-Wei; Kuo, Chi-Tai; Chen, Jin-Jer; Chen, Zhih-Cherng; et al.
Abstract : Objective: To evaluate whether home or ambulatory blood pressure (BP) monitoring was associated with preclinical hypertensive cardiovascular target organ damage (TOD). Methods: We enrolled participants with prehypertension and stage 1 hypertension from 11 medical centers within the Taiwan hypertension-associated cardiac disease consortium. Recordings of clinical BP measurement, ambulatory BP monitoring for 24 hours, and home BP monitoring during morning and evening were made. The measured parameters of target organ damage included left ventricular mass index (LVMI), left atrial volume index (LAVI), and carotid-femoral pulse wave velocity (PWV). Results: Data were collected from 561 study participants (mean age, 65.0 ± 10.8 years; men, 61.3%). Morning and evening home BP values were slightly higher than the daytime and nighttime ABP values (difference for systolic morning-daytime/evening-nighttime, 7.3 ± 14.2/11.3 ± 18.5 mm Hg, P < .001; for diastolic, 5.4 ± 9.4/7.3 ± 12.1, P < .001). Daytime ambulatory ( r = 0.114), nighttime ambulatory ( r = 0.130), morning home ( r = 0.310), and evening home ( r = 0.220) systolic BPs (SBPs) were all associated with LVMI (all P < .05). The correlation coefficient was significantly greater for the relationship between daytime home SBP and LVMI than for the relationship between ambulatory SBP and LVMI ( P < .01). The goodness of fit of the association between SBP and LVMI improved by adding home daytime SBP to the other SBPs ( P < .001). Similar findings were observed for LAVI, but not for PWV. Conclusion: These findings indicate that morning SBP assessed by home monitoring appears to be a better predictor than other BP measures to determine preclinical hypertensive cardiovascular damage in patients with early-stage hypertension. Abstract : Supplemental digital content is available in the text.